Preparation method of inorganic-organic hybrid modified pine wood

By generating phosphorus nitrogen/rosin ester hybrid flame retardant in the micropores of pine wood, processing difficulties and flammability problems caused by pine resin in pine wood are solved, and efficient flame retardant and loss resistance are achieved, which enhances the utilization value of pine wood.

CN120533798APending Publication Date: 2025-08-26CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510424719.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The high content of pine wood has caused difficulty in processing, aesthetics and durability. At the same time, pine wood is flammable and flame retardant is easily lost. The existing treatment methods have problems of environmental pollution and high cost.

Method used

The inorganic-organic hybrid modification method of phosphorus-nitrogen flame retardant, boric acid and polyol is used to generate phosphorus-nitrogen/rosin ester hybrid flame retardant in situ in the micropores of pine wood through vacuum-pressurized impregnation and water bath heat reaction, forming an expanded flame retardant, improving the flame retardant performance and improving the influence of rosin.

Benefits of technology

It significantly improves the flame retardant properties and loss resistance of pine wood, solves the negative impact of pine resin on processing and aesthetics, and has a simple process and low cost, which promotes the efficient utilization of pine wood.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120533798A_ABST
    Figure CN120533798A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of wood preparation, and discloses a preparation method of inorganic-organic hybrid modified pine, which comprises the following steps: drying pine sawn timber; the dried pine wood is placed in a vacuum impregnation tank to be subjected to vacuum-pressure impregnation with modified impregnation liquid, and the modified impregnation liquid contains a phosphorus-nitrogen flame retardant, boric acid and polyhydric alcohol; and taking out the impregnated pine, cleaning, carrying out a water bath thermal reaction, and drying after the reaction is finished to obtain the inorganic-organic hybrid modified pine. According to the invention, an acidic solution of a phosphorus-nitrogen flame retardant and boric acid is used as a reaction medium for esterification reaction of rosin and polyol, rosin is used as a substrate, polyol is used as a reactant, and in-situ esterification reaction of rosin and polyol is realized in pore channels of wood to synthesize the phosphorus-nitrogen / rosin ester hybridized intumescent flame retardant. According to the invention, the flame-retardant property of pine wood can be improved, flame propagation is prevented, the loss resistance of the flame retardant is improved, and the influence of rosin exudation on wood quality can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wood preparation, and in particular relates to a method for preparing phosphorus nitrogen / rosin ester inorganic-organic hybrid modified pine wood. Background Art

[0002] Pine is one of the most widely used wood species in the world. Due to its good mechanical properties, easy processing and natural and beautiful texture, pine is widely used in building structures, furniture manufacturing and decorative materials.

[0003] However, pine wood contains significant amounts of rosin, typically accounting for 3-10% of the wood's weight, with this percentage even higher in certain high-resin pine woods. This component often presents numerous drawbacks during wood processing and use. For example, high rosin content increases the wood's stickiness, leading to increased tool wear and reduced processing efficiency. Furthermore, rosin leakage can affect the wood's aesthetics and service life. Traditional approaches to address this issue include degreasing, such as through high-temperature treatment, solvent extraction, and chemical treatment. While these methods can mitigate the effects of rosin to some extent, they also have significant drawbacks. For example, high-temperature treatments exceeding 200°C can damage the wood's internal structure, reducing its mechanical properties and durability. While solvent extraction or chemical treatments are relatively effective, they also pose environmental risks, health risks, and are costly. Therefore, effectively reducing or rationally utilizing rosin without compromising wood properties has become a pressing issue in pine wood processing.

[0004] In addition, pine wood is extremely flammable and releases a large amount of heat and smoke when burning, posing a huge safety hazard. The frequent occurrence of wooden structure fires in recent years has not only seriously affected people's daily production and life, but also posed a serious threat to life and property. Studies have shown that reducing the flammability of wood and inhibiting the production of smoke and toxic gases during combustion will help to safely evacuate people in a fire and minimize fire losses. At present, researchers have developed a variety of wood flame retardant treatment technologies, among which impregnation flame retardant treatment is currently the most effective method to improve the flame retardancy of wood. However, a major disadvantage of impregnation flame retardant treatment is that the flame retardant is easy to absorb moisture and lose during use, which seriously affects the durability of the modified wood. At present, an effective strategy to deal with this problem is to form a hydrophobic network structure or interface inside the wood through the reaction of polymer resins or organic compounds to slow down the loss of flame retardants. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a preparation method of phosphorus nitrogen / rosin ester inorganic-organic hybrid modified pine wood.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing inorganic-organic hybrid modified pine wood comprises the following steps: (1) subjecting pine sawn timber to a gradient drying process; (2) placing the pine wood dried in step (1) in a vacuum impregnation tank for vacuum-pressure impregnation to obtain a modified impregnation solution, wherein the modified impregnation solution contains a phosphorus-nitrogen flame retardant, boric acid, and a polyol; (3) After the impregnation, the pine wood is taken out and cleaned, and then subjected to a water bath heat reaction. After the reaction is completed, it is dried to obtain an inorganic-organic hybrid modified pine wood.

[0007] In the above-mentioned preparation method, preferably, in step (2), the specific process of the vacuum-pressure impregnation includes: placing the dried pine wood in an impregnation tank, evacuating the tank to -0.07~-0.1MPa, maintaining the negative pressure for 0.5~1.0h, then injecting the modified impregnation liquid, and then pressurizing the tank to 1.2~3.0MPa and continuing the impregnation for 2~4h.

[0008] In the above preparation method, preferably, in step (2), the negative pressure stage maintains a pressure of -0.09 MPa for 1 hour, and the pressurized stage maintains a pressure of 2.5 MPa for 3 hours.

[0009] In the above preparation method, preferably, in step (2), the phosphorus-nitrogen flame retardant is selected from at least one of ammonium polyphosphate, ammonium phosphate, ammonium hydrogen phosphate, and ammonium dihydrogen phosphate; and the polyol is glycerol or pentaerythritol.

[0010] In the above preparation method, preferably, in step (2), the mass ratio of the phosphorus-nitrogen flame retardant and boric acid is (3-5):1, and the added amount of the polyol is 6wt%-12wt% of the total mass of the modified impregnation solution.

[0011] In the above preparation method, preferably, in step (2), the pH of the impregnation solution is adjusted to 2-6 by adjusting the amount of boric acid.

[0012] In the above preparation method, preferably, in step (1), the drying treatment includes first drying in stages at a temperature within a range of 30 to 80°C, and then drying at 105°C until absolutely dry.

[0013] In the above preparation method, preferably, in step (3), the drying treatment includes drying in stages at a temperature between 25° C. and 80° C. to an equilibrium moisture content of 8% to 15%.

[0014] In the above preparation method, preferably, in step (3), the wood is taken out and rinsed with deionized water to remove excess liquid on the surface, and then sealed with polypropylene film and aluminum foil and reacted in a water bath. The water bath thermal reaction temperature is 100°C and the reaction time is 6-12 hours.

[0015] In the above preparation method, preferably, a needle-shaped phosphorus nitrogen / rosin ester composite flame retardant is in-situ generated in the pores of the inorganic-organic hybrid modified pine wood, and the residual carbon layer has a honeycomb expansion structure.

[0016] Rosin is primarily composed of diterpenoid resin acids, whose chemical structure contains double bonds and carboxyl groups, resulting in high reactivity. Through appropriate chemical modifications, such as esterification, rosin can be converted into high-value chemical products, such as rosin polyol esters. Rosin polyol esters are known for their excellent stability and curing properties. In light of this, the present invention innovatively utilizes the natural pore structure of pine wood as a microreactor, achieving an in-situ esterification reaction of rosin and polyols within the wood at relatively low temperatures. The specific technical solution utilizes an acidic solution of a phosphorus-nitrogen flame retardant as a medium, boric acid (BA) as a catalyst, rosin as a substrate, and polyols (such as glycerol and pentaerythritol) as reagents. Through low-temperature heat treatment, a phosphorus-nitrogen / rosin ester hybrid inorganic-organic intumescent flame retardant is generated in situ within the wood's micropores. This hybrid flame retardant exhibits similar properties to intumescent flame retardants. It not only significantly improves the flame retardancy of pine wood and prevents flame propagation through charring, but also enhances the flame retardant's resistance to leaching due to the hydrophobicity of the ester. It also effectively mitigates the impact of rosin exudation on wood quality. This method has a simple process and can effectively improve the flame retardant properties of wood while further solving the drawbacks of pine resin in pine wood on wood processing and surface aesthetics, thereby promoting the efficient utilization of pine wood and improving its functionality.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses an acidic solution of phosphorus-nitrogen flame retardant and boric acid (BA) as a reaction medium for the esterification reaction between rosin and polyols, rosin as a substrate, polyols (glycerol, pentaerythritol, etc.) as reactants, and the natural microporous structure of pine wood as a "microreactor". The in-situ esterification reaction of rosin and polyols is realized inside the pores of the wood to synthesize a phosphorus-nitrogen / rosin ester hybrid intumescent flame retardant. This not only significantly improves the flame retardant properties of pine wood and prevents flame propagation by expanding into charcoal, but also improves the anti-loss property of the flame retardant through the hydrophobicity of the ester, and can effectively improve the effect of rosin exudation on wood quality.

[0018] (2) The process of the present invention is simple. While effectively improving the flame retardant properties of wood, it can further solve the disadvantages of pine resin in pine wood on wood processing and surface aesthetics, thereby promoting the efficient utilization of pine wood and improving its functionality. The process flow is low in cost and has good effect, and is worthy of promotion. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 These are infrared spectra of rosin esterification products of the modified impregnation solution in different reactors of the present invention.

[0020] Figure 2 : This is a comparison of the Fourier transform infrared spectra of the pine wood material (control) and the phosphorus nitrogen-rosin ester hybrid modified pine wood (Pine (ADP+BA)+C3) obtained in Example 1.

[0021] Figure 3 The X-ray diffraction comparison charts are for pine wood material, pine wood treated with ADP and BA impregnation solution in Comparative Example 1 (Pine (ADP+BA)), and phosphorus nitrogen-rosin ester hybrid modified pine wood obtained in Example 1.

[0022] Figure 4 The microstructure scanning electron microscope images of the cross section and profile of the pine wood material and the phosphorus nitrogen-rosin ester hybrid modified pine wood sample obtained in Example 1.

[0023] Figure 5 This is a comparison chart of the total heat release and total smoke release of the modified pine wood sample and the pine wood material sample obtained in Example 1 and Comparative Example 1 in the cone calorimetry test.

[0024] Figure 6 These are photos and SEM images of the char residues after ignition of the modified pine wood samples and pine wood material samples obtained in Example 1 and Comparative Example 1.

[0025] Figure 7 This is a comparison chart of surface color parameters of the modified pine wood sample and the pine wood material sample obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0026] To facilitate understanding of the present invention, the present invention will be described in more comprehensive and detailed form below in conjunction with the accompanying drawings and preferred embodiments. However, the protection scope of the present invention is not limited to the following specific embodiments.

[0027] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0029] Comparative study of rosin esterification reaction using modified impregnation solution in different reactors. The specific steps are as follows: (1) ammonium dihydrogen phosphate (ADP) and boric acid (BA) in a mass ratio of 4:1 were mixed with water to form a mixed solution with a total mass concentration of 30 wt.%, and glycerol (C3) accounting for 9.0 wt.% of the total impregnation solution was added to obtain a modified impregnation solution for standby use; (2) The modified impregnation solution prepared in step (1) was divided into three parts and added to a 25 mL beaker, a 1 mm glass capillary and a 1 mm glass capillary for parallel testing. Then, rosin powder was added respectively, wherein the molar mass ratio of rosin powder to glycerol in the modified impregnation solution was 3:1. The glass capillary and the beaker were sealed with high-temperature resistant plastic wrap and tin foil, and then heated at 100 ° C (beaker), 80 ° C (glass capillary) and 100 ° C (glass capillary) for 12 hours.

[0030] Figure 1 The infrared spectrum of the product obtained by simulating the esterification reaction of the modified impregnation liquid using a capillary as a "microreactor". By comparison, it can be found that the product obtained by using a glass capillary to simulate the reaction of the modified impregnation liquid in a "microreactor" at 100℃ for 12 hours has a clear ester group characteristic peak (1733cm -1 ), indicating that esterification occurred between rosin and glycerol in the acidic medium composed of ammonium dihydrogen phosphate and boric acid. Furthermore, the product obtained in the capillary-simulated "microreactor" after a 12-hour reaction at 80°C contained only a weak shoulder peak characteristic of the ester group, suggesting that a reaction temperature of 100°C is more suitable. However, the product obtained after a 12-hour reaction at 100°C in a flask containing the modified impregnation solution failed to exhibit the characteristic ester group peak. Compared to the aforementioned reaction using a glass capillary, this demonstrates that the "microreactor" indeed promotes the esterification reaction.

[0031] Example 1: A method for preparing inorganic-organic hybrid modified pine wood of the present invention comprises the following steps: (1) Rinse the surface of the pine sawn timber with deionized water and place it in a blast drying oven for segmented drying. Specifically, dry it at 40°C for 8 hours, 60°C for 6 hours, 80°C for 6 hours, and 105°C for 4 hours until it is completely dry and set aside.

[0032] (2) Ammonium dihydrogen phosphate (ADP) and boric acid (BA) in a mass ratio of 4:1 were mixed with water to form a mixed solution with a total mass concentration of 30 wt.%, and glycerol (C3) accounting for 9.0 wt% of the total impregnation solution was added to obtain a modified impregnation solution for standby use.

[0033] (3) The wood after drying in step (1) is placed in a vacuum impregnation tank, vacuumed to -0.09 MPa and maintained for 1 hour; then the modified impregnation liquid in step (2) is introduced into the impregnation tank, and then pressurized to 2.5 MPa and maintained constant pressure for 3 hours.

[0034] (4) The surface of the pine wood treated in step (3) was rinsed with deionized water and wiped dry, then tightly wrapped with polypropylene film and aluminum foil in sequence, and then transferred to a 100°C constant temperature water bath for water bath treatment for 12 hours, then taken out to dry, and then placed in a forced air drying oven and dried at 40°C for 8 hours, 60°C for 6 hours, and 80°C for 6 hours in sequence until the equilibrium moisture content was 12%, thereby obtaining phosphorus nitrogen-rosin glycerol ester hybrid modified pine wood.

[0035] Comparative Example 1: The only difference between Comparative Example 1 and Example 1 is that glycerol (C3) is not added in step (2), and other process parameters and conditions remain the same as those in Example 1.

[0036] Figure 2 The following is a comparison of the Fourier transform infrared spectra of pine wood (control) and the phosphorus nitrogen-rosin ester hybrid modified pine wood (Pine (ADP + BA) + C3) obtained in Example 1. The comparison shows that the modified pine wood in Example 1 has a clear characteristic peak of the ester group (1733 cm -1 ), which shows that the rosin and glycerol in the pine wood did undergo in-situ esterification in the acidic solution of ADP and BA to produce rosin esters, which is consistent with the Figure 1 The conclusion is consistent with that of using capillary to simulate "microreactor".

[0037] Figure 3Comparative X-ray diffraction patterns of pine wood, pine wood treated with the ADP and BA impregnation solution in Comparative Example 1 (Pine (ADP+BA)), and the phosphorus-nitrogen-rosin ester hybrid-modified pine wood obtained in Example 1. The results show that both the pine wood treated with the ADP and BA impregnation solution in Comparative Example 1 and the phosphorus-nitrogen-rosin ester hybrid-modified pine wood obtained in Example 1 exhibit distinct characteristic peaks of ammonium dihydrogen phosphate at 16.6°, 23.6°, and 29°, indicating that the flame retardant has been incorporated into the wood. Furthermore, the diffraction peak at 22.0° remains virtually unchanged, indicating that the cellulose lattice of the pine wood has not been significantly damaged by the treatment. However, the intensity of the diffraction peak at 16.2° weakens for both materials, and their crystallinity decreases from 39.86% of the original material to 32.86% and 35.99%, respectively. This is likely due to the ADP / BA entering the crystalline region of cellulose, disrupting the hydrogen bonding between or within the cellulose molecules to some extent, thereby affecting its crystallinity.

[0038] Figure 4 The cross-section and microstructure scanning electron microscope images of the pine wood material and the phosphorus nitrogen-rosin ester hybrid modified pine wood sample obtained in Example 1. Figure 4 (a, b) It can be seen that the pores of the pine wood treated in Example 1 are filled with a large amount of needle-shaped composite flame retardant formed by the phosphorus nitrogen-glyceride composite. This demonstrates that the treatment of the present invention can cause the rosin and glycerol in the pine wood to react in situ to form the phosphorus nitrogen / rosin glyceride organic composite flame retardant.

[0039] Flame retardant properties: The pine wood samples used in the experiment were processed from their sapwood. According to ISO5660-1 standard, 100mm×100mm×10mm test materials were selected. The wood samples were ignited using a cone calorimeter. The experiment was carried out at a thermal radiation intensity of 50 kW / m 2 The heat release and smoke release parameters of wood can be obtained under different conditions.

[0040] Figure 5 This figure compares the total heat release and total smoke release from cone calorimetry tests of modified pine wood samples obtained in Example 1 and Comparative Example 1, compared to raw pine wood samples. The test results demonstrate that the modified pine wood sample in Example 1 exhibits excellent flame retardancy, with its heat release rate reduced by 95.49% and smoke release by 53.84% compared to the raw material. This is attributed to the fact that the inorganic-organic intumescent flame retardant, formed by the phosphorus-nitrogen / rosin ester hybrid, significantly enhances the flame retardancy and smoke suppression properties of pine wood by expanding into charcoal.

[0041] Figure 6The photographs and SEM images of the char residues from the modified pine wood samples and the pine wood sample obtained in Example 1 and Comparative Example 1 clearly show that only a small amount of white ash remains after the pine wood is burned. The pine wood treated in Comparative Example 1 produces char after ignition, but its appearance remains virtually unchanged. The char residue from the pine wood treated in Example 1 exhibits significant volume expansion after ignition, and SEM microstructure observation of the char residue reveals significant foaming in the char layer. This fully demonstrates that the phosphorus-nitrogen-rosin ester hybrid flame retardant functions as an intumescent flame retardant, providing excellent flame retardancy for wood.

[0042] Color difference analysis: The effect of the modification treatment on the surface color of the specimens can be studied using a colorimeter (3nh, model NR100QC). Six points are measured for each sample and the average value is calculated. The untreated material is used as a control group to analyze the total color difference change (ΔE*) of the specimens. ΔE* can be calculated using formula (1).

[0043]

[0044] Note: ΔL* is the difference in lightness value of the sample surface before and after immersion treatment. The extreme values ​​of ΔL∗ are 0 and 100. The larger the value, the whiter the wood surface, and vice versa. Δa* is the difference in the red-green axis parameter of the sample surface before and after immersion treatment. The larger Δa* is, the redder the wood surface color is, and vice versa. Δb* is the difference in the yellow-blue axis parameter of the wood sample surface before and after immersion treatment. The larger Δb* is, the yellower the wood surface color is, and vice versa.

[0045] Figure 7 The surface color parameters of the modified pine wood samples obtained in Example 1 and Comparative Example 1, as well as the original pine wood sample, are shown. In terms of lightness, the lightness of the pine wood treated in Comparative Example 1 decreased slightly, while the lightness of the pine wood treated in Example 1 remained almost unchanged from the original sample. This decrease in lightness is due to the acidity of the component (sodium dihydrogen phosphate) in the phosphorus-nitrogen flame retardant, which causes the migration and diffusion of chromophores and auxochromes on the wood surface. However, the polyol groups of glycerol / pentaerythritol bind to the hydroxyl groups on the wood surface, inhibiting the migration of these chromophores, thereby helping the wood maintain its original lightness. Furthermore, the hydrophilicity of glycerol / pentaerythritol facilitates the diffusion of the flame retardant within and on the wood surface, further contributing to a decrease in lightness. Similarly, the total color difference change (ΔE*) shows that the color difference of the pine wood modified in Comparative Example 1 changes significantly, resulting in a noticeable change in the wood's surface color. In contrast, the total color difference change of the pine wood modified in Example 1 is relatively small, and the wood maintains its original color.

[0046] Anti-loss performance: The pine wood used in the experiment was processed from sapwood. Following the requirements of the national standard GB / T 29905-2013, seven pine wood samples from each group, each from Comparative Example 1 and Example 1, were placed in a 500mL beaker and filled with 300mL of deionized water. The leachate-containing water was then replaced five times, at intervals of 6, 24, 48, 48, and 48 hours. As shown in Table 1, the flame retardant mass loss rate of the pine wood samples modified in Comparative Example 1 after 7 days of water immersion was as high as 92.1%, indicating that ADP and BA possess little anti-loss performance. In contrast, the flame retardant mass loss rate of the pine wood samples modified in Example 1 after 14 days of water immersion was 42.2%, which is attributed to the hydrophobicity of the rosin esters generated in situ within the wood pores, which inhibits water intrusion and thus improves flame retardant loss.

[0047] Example 2: A method for preparing inorganic-organic hybrid modified pine wood of the present invention comprises the following steps: (1) Rinse the surface of the pine sawn timber with deionized water and place it in a blast drying oven for segmented drying. Specifically, dry it at 40°C for 8 hours, 60°C for 6 hours, 80°C for 6 hours, and 105°C for 4 hours until it is completely dry and set aside.

[0048] (2) A mixed solution of ammonium dihydrogen phosphate (ADP) and boric acid (BA) in a mass ratio of 3:1 and water with a total mass percentage of 24 wt.% was prepared, and then pentaerythritol accounting for 12 wt.% of the total mass percentage of the impregnation solution was added to obtain a modified impregnation solution for standby use.

[0049] (3) The wood after drying in step (1) is placed in a vacuum impregnation tank, vacuumed to -0.09 MPa and maintained for 1 hour; then the modified impregnation liquid in step (2) is introduced into the impregnation tank, and then pressurized to 2.0 MPa and maintained constant pressure for 4 hours.

[0050] (4) The surface of the pine wood treated in step (3) was rinsed with deionized water and wiped dry, then tightly wrapped with polypropylene film and aluminum foil in sequence, and then transferred to a 100°C constant temperature water bath for water bath treatment for 12 hours, then taken out to dry, and then placed in a forced air drying oven and dried at 40°C for 8 hours, 60°C for 6 hours, and 80°C for 6 hours in sequence until the equilibrium moisture content was 12%, thereby obtaining phosphorus nitrogen-rosin glycerol ester hybrid modified pine wood.

[0051] The total heat release and total smoke release of the modified pine wood samples and the original pine wood samples in Example 2 were measured using the same testing method as in Example 1. The test results demonstrated that the modified pine wood samples in Example 2 exhibited excellent flame retardancy, with heat release rates reduced by 91.44% and smoke release rates by 51.47% compared to the original pine wood samples.

[0052] The anti-water loss performance of the modified pine wood sample and the pine wood material sample in Example 2 was measured using the same test method as in Example 1. As shown in Table 1, the anti-water loss rate of the modified pine wood sample in Example 2 after 14 days of water immersion test was 46.5%.

[0053] Example 3: A method for preparing inorganic-organic hybrid modified pine wood of the present invention comprises the following steps: (1) Rinse the surface of the pine sawn timber with deionized water and place it in a blast drying oven for segmented drying. Specifically, dry it at 40°C for 8 hours, 60°C for 6 hours, 80°C for 6 hours, and 105°C for 4 hours until it is completely dry and set aside.

[0054] (2) A mixed solution of ammonium dihydrogen phosphate (ADP), boric acid (BA) and water in a mass ratio of 5:1 was prepared to a total mass percentage of 24 wt.%, and glycerol accounting for 6 wt.% of the total mass percentage of the impregnation solution was added to obtain a modified impregnation solution for standby use.

[0055] (3) The wood after drying in step (1) is placed in a vacuum impregnation tank, vacuumed to -0.09 MPa and maintained for 1 hour; then the modified impregnation liquid in step (2) is introduced into the impregnation tank, and then pressurized to 2.0 MPa and maintained constant pressure for 3 hours.

[0056] (4) The surface of the pine wood treated in step (3) was rinsed with deionized water and wiped dry, then tightly wrapped with polypropylene film and aluminum foil in sequence, and then transferred to a 100°C constant temperature water bath for water bath treatment for 12 hours, then taken out to dry, and then placed in a forced air drying oven to dry at 40°C for 8 hours, 60°C for 6 hours, and 80°C for 6 hours until the equilibrium moisture content was 12%, thereby obtaining phosphorus nitrogen-rosin glycerol ester hybrid modified pine wood.

[0057] The total heat release and total smoke release of the modified pine wood samples and the original pine wood samples in Example 3 were measured using the same testing method as in Example 1. The test results demonstrated that the modified pine wood samples in Example 3 exhibited excellent flame retardancy, with heat release rates reduced by 98.14% and smoke release rates by 58.34% compared to the original pine wood samples.

[0058] The anti-water loss performance of the modified pine wood sample and the pine wood material sample in Example 3 was measured using the same test method as in Example 1. As shown in Table 1, the anti-water loss rate of the modified pine wood sample in Example 3 after 14 days of water immersion test was 48.3%.

[0059] Example 4: A method for preparing inorganic-organic hybrid modified pine wood of the present invention comprises the following steps: (1) Rinse the surface of the pine sawn timber with deionized water and place it in a blast drying oven for segmented drying. Specifically, dry it at 40°C for 8 hours, 60°C for 6 hours, 80°C for 6 hours, and 105°C for 4 hours until it is completely dry and set aside.

[0060] (2) A mixed solution of ammonium dihydrogen phosphate (ADP) and boric acid (BA) in a mass ratio of 4:1 and water with a total mass percentage of 30 wt.% was prepared, and then pentaerythritol accounting for 12 wt.% of the total mass percentage of the impregnation solution was added to obtain a modified impregnation solution for standby use.

[0061] (3) The wood after drying in step (1) is placed in a vacuum impregnation tank, vacuumed to -0.09 MPa and maintained for 1 hour; then the modified impregnation liquid in step (2) is introduced into the impregnation tank, and then pressurized to 2.5 MPa and maintained constant pressure for 3 hours.

[0062] (4) The surface of the pine wood treated in step (3) was rinsed with deionized water and wiped dry, then tightly wrapped with polypropylene film and aluminum foil in sequence, and then transferred to a 100°C constant temperature water bath for water bath treatment for 12 hours. Subsequently, it was taken out to dry, and then placed in a forced air drying oven to dry at 40°C for 8 hours, 60°C for 6 hours, and 80°C for 6 hours in sequence. The equilibrium moisture content was 12%, and phosphorus nitrogen-rosin glycerol ester hybrid modified pine wood was obtained.

[0063] The total heat release and total smoke release of the modified pine wood samples and the original pine wood samples in Example 4 were measured using the same testing method as in Example 1. The test results demonstrated that the modified pine wood samples in Example 4 exhibited excellent flame retardancy, with heat release rates reduced by 96.87% and smoke release rates by 54.58% compared to the original pine wood samples.

[0064] The anti-water loss performance of the modified pine wood sample and the pine wood material sample in Example 4 was measured using the same test method as in Example 1. As shown in Table 1, the anti-water loss rate of the modified pine wood sample in Example 4 after 14 days of water immersion test was 42.1%.

[0065] Table 1 Comparative data on the anti-loss performance of pine wood after 7-day water immersion test after phosphorus nitrogen-rosin ester composite modification

[0066] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing inorganic-organic hybrid modified pine wood, characterized in that: The following steps are involved: (1) subjecting pine sawn timber to a gradient drying process; (2) placing the pine wood dried in step (1) in a vacuum impregnation tank for vacuum-pressure impregnation to obtain a modified impregnation solution, wherein the modified impregnation solution contains a phosphorus-nitrogen flame retardant, boric acid, and a polyol; (3) After the impregnation, the pine wood is taken out and cleaned, and then subjected to a water bath heat reaction. After the reaction is completed, it is dried to obtain an inorganic-organic hybrid modified pine wood.

2. The preparation method according to claim 1, wherein In step (2), the specific process of the vacuum-pressure impregnation includes: placing the dried pine wood in an impregnation tank, evacuating the tank to -0.07~-0.1MPa, maintaining the negative pressure for 0.5~1.0h, then injecting the modified impregnation liquid, and then pressurizing the tank to 1.2~3.0MPa for impregnation for 2~4h.

3. The preparation method according to claim 2, wherein In step (2), the negative pressure stage maintained the pressure at -0.09 MPa for 1 hour, and the pressurized stage maintained the pressure at 2.5 MPa for 3 hours.

4. The preparation method according to claim 1, wherein In step (2), the phosphorus-nitrogen flame retardant is selected from at least one of ammonium polyphosphate, ammonium phosphate, ammonium hydrogen phosphate, and ammonium dihydrogen phosphate; and the polyol is glycerol or pentaerythritol.

5. The preparation method according to claim 1, wherein In step (2), the mass ratio of the phosphorus-nitrogen flame retardant and boric acid is (3-5):1, and the added amount of the polyol is 6wt%-12wt% of the total mass of the modified impregnation solution.

6. The preparation method according to claim 1, wherein In step (1), the drying process includes drying in stages at a temperature in the range of 30 to 80° C., and then drying at 105° C. until the mixture is absolutely dry.

7. The preparation method according to claim 1, wherein In step (3), the drying process includes drying in stages at a temperature between 25° C. and 80° C. to an equilibrium moisture content of 8% to 15%.

8. The preparation method according to claim 1, wherein In step (3), the water bath thermal reaction temperature is 100°C, and the reaction time is 6-12 hours.

9. The preparation method according to claims 1 to 8, characterized in that: A needle-shaped phosphorus nitrogen / rosin ester composite flame retardant is in-situ generated in the pores of the inorganic-organic hybrid modified pine wood, and the residual carbon layer has a honeycomb expansion structure.